Conditionality, discretion and TH Marshall's 'right to welfare'. Issue 4 (2nd October 2019) - Fitzpatrick, Ciara; McKeever, Gráinne; Simpson, Mark
ABSTRACT: In an era of increasing interest in and concern about destitution in the UK, the leading studies place social security problems among the principal causes. This suggests that destitution is a failure of social citizenship, with social protection systems unable or unwilling to underwrite the guarantee of a modicum of economic welfare that, according to Marshall, forms the essence of the citizen's social rights. This article documents how the establishment of a comprehensive welfare state in the mid-20 th century has been eroded by a series of social security reforms that have turned the focus back on local government and the voluntary sector for the support of the 'undeserving' migrant and unemployed poor. Empirical findings from a major study of destitution in the UK illustrate how the fulfilment of social 'rights' is becoming dependent on knowing where to seek support, having access to the right gatekeeper and enduring social stigma. The authors consider the compatibility of a welfare state characterised by strict conditionality, decision maker discretion and gaps in the safety net with the Marshallian 'right to welfare'.